Farmer innovation system and government intervention: an empirical study of straw utilisation technology development and diffusion in China - Zhang, Liyan; Wu, Bin (Elsevier, 2018)
In the context of rural sustainability in the developing world, a dilemma facing government intervention is to recognise and properly use local (or indigenous, practical) knowledge. This paper sheds new light on government intervention by introducing a farmer innovation system (FIS), which is initiated by farmer innovator(s) with participation or support from government agencies and other stakeholders for technology improvement and diffusion. In relation to different understandings, attitudes and approaches to farmer innovation, we argue that different government intervention may lead to different project designs and results. The complexity of government intervention in farmer innovation can be seen from an empirical study of the development and diffusion of straw utilisation technology (SUT) in rural China. By analysing and comparing two cases - one successful and one failed - we reveal two types of government intervention, and features and conditions of project success. The major limitation is identified as leaving out other actors such as local business partners and non-government agencies. We suggest a balanced account between farmer innovator(s), government intervention and innovation platform in future research.